An efficient algorithm for capturing quantum effects in classical reactive scattering: application to D + H+3 → H2D+ + H. Issue 3 (21st December 2022) - Braunstein, Matthew; Bonnet, Laurent
Abstract : Thermal rate constant versus temperature for 1GB-Cav, ZPE-Cav, RPMD (RPMDdir: [Bulut et al., J. Phys. Chem. A, 2019, 123, 8766]), and experimentally derived results (Bowen [Bowen et al., J. Chem. Phys., 2021, 154, 084307]). Abstract : Motivated by a recent semiclassical analysis of chemical reaction thresholds [Bonnet et al., J. Chem. Phys., 2022, 157, 094114], we present an efficient algorithm for including zero-point energy (ZPE) effects in classical reactive scattering. The algorithm is an extension of the quasi-classical trajectory (QCT) Gaussian binning method. We apply it to the astrophysically important D + H+3 reaction, where there are significant quantum effects and where application of other methods is problematic [Braunstein et al., Phys. Chem. Chem. Phys., 2022, 24, 5489]. The rate constants computed with the new, general algorithm closely match recent Ring Polymer Molecular Dynamics (RPMD) [Bulut et al., J. Phys. Chem. A, 2019, 123, 8766] and experimentally derived [Bowen et al., J. Chem. Phys., 2021, 154, 084307] ones spanning ∼4 orders of magnitude from 70 to 1500 K.